2020
DOI: 10.1504/ijpqm.2020.111700
|View full text |Cite
|
Sign up to set email alerts
|

Local brand franchise competition in the disruption era

Abstract: Local brand franchise business, particularly culinary, has been rapidly developed in this disruption era. This is in line with the society's need for delicious but affordable culinary. There is a comprehensive relation-blend of cultural, business, and lifestyle responses. This research examined the factors affecting local brand franchises in the business competition in the disruption era. Using a descriptive qualitative method, the results indicated that local brand franchises are a part of economic disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Moreover, it encourages consumer engagement in marketing activities via social media and fosters wordof-mouth recommendations, reflecting local wisdom and economic sharing (Subawa & Widhiasthini, 2020). It includes the circulation of the great content on the profile of social media, listening to and gets engage with the followers, and running social media advertisements.…”
Section: Literature Review Social Media Marketingmentioning
confidence: 99%
“…Moreover, it encourages consumer engagement in marketing activities via social media and fosters wordof-mouth recommendations, reflecting local wisdom and economic sharing (Subawa & Widhiasthini, 2020). It includes the circulation of the great content on the profile of social media, listening to and gets engage with the followers, and running social media advertisements.…”
Section: Literature Review Social Media Marketingmentioning
confidence: 99%
“…The growing use of social media changed the marketplaces extremely and this paradigm shift has made the consumers more powerful by giving them more opportunities to interact with producers before they are making purchase decisions (Subawa & Widhiasthini, 2020). Within the digital disruption era, the earlier producer/marketer-centric hegemony now has been transferred towards consumers, where they can manipulate the purchase decision of others.…”
Section: Consumer Hegemony On Social Mediamentioning
confidence: 99%
“…Within the digital disruption era, the earlier producer/marketer-centric hegemony now has been transferred towards consumers, where they can manipulate the purchase decision of others. Digital democracy and the young generations' technological dominance (Subawa & Widhiasthini, 2020) have major implications over marketing strategies made by organisations, and consumer purchasing behaviors while the consumers have become marketing agents. Chaker et al (2022) explained this has turned consumers into "prosumers" who influence businesses through electronic word of mouth.…”
Section: Consumer Hegemony On Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneurs should start actively studying and making updates related to technology. Results of the research of Aulia (2021); da Silveira et al, (2021); Fan et al, (2021); Lynch et al, (2021); Ritz et al, (2019); Oberoi et al, (2021); Siagian et al, (2021); Subawa et al, (2020) concluded that in the changing era of disruption, humans elaborate with information systems and technology, the main goal is to improve the quality of human resources. This is also supported in the research of Dong et al (2020); Faling & Biesbroek (2019); Tajvidi et al (2021); Zhao et al (2021), who stated that the use of digital in entrepreneurship will provide many positive benefits for business success and can provide many conveniences in carrying out entrepreneurial activities.…”
Section: Introductionmentioning
confidence: 99%